Effect of pre-germination at varying stages of embryonic growth length on chemical composition and protein profile of Thai rice (Oryza sativa L.) - Kupkanchanakul, Warunee; Kadowaki, Motoni; Kubota, Masatoshi; Naivikul, Onanong (Agriculture and Natural Resources, 2018)
The effect of pre-germination at varying stages of embryonic growth length (EGL) (0.5-7 mm, for 30-56 h of pre-germination time) on the chemical composition and protein profiles were investigated in three different Thai rice cultivars-SPT1 (waxy), PTT1 (low amylose), and PNL2 (high amylose). Pre-germination at 0.5-1 mm of EGL (first-stage) of all rice led to a significant change in most of the total starch, crude protein, and crude fat contents except in the crude protein content of PNL2 and the crude fat content of SPT1, which significantly changed at 3-7 mm of EGL (malted-stage) and at 2-3 mm of EGL (third-stage), respectively. Analysis of protein profiles from all rice samples indicated that glutelin molecules existed in subunits linked by disulfide bonds. Pre-germination to the second-stage of SPT1 and PTT1, and to the first-stage of PNL2 caused the cleavage of proglutelin ( 51.6 kDa) into acidic-glutelin ( 31.9 kDa) and basic-glutelin ( 17.8 kDa) and also increased the relative concentration of 13 kDa prolamins. Pre-germination of these three rice cultivars at 30°C for 32-48 h clearly indicated the function as bio-modification of rice proteins, particularly in the reduction of glutelin disulfide bonds.